VERTICAL ASYMMETRY OF RIVER CHANNEL CROSS-SECTIONS: A STUDY ON A MORIBUND DELTAIC CHANNEL - DAS, B. C. (Studia Universitatis Babeș-Bolyai Geographia, 2015)
Vertical Asymmetry of River Channel Cross-Sections: a Study on a Moribund Deltaic Channel. Channel asymmetry has been quantified in three indices by Knighton (1981). His work has opened the wide porthole to have a search on every nook and corner of problems associated with channel asymmetry. The asymmetry of the river channel cross section is measured both horizontally and vertically. Horizontal asymmetry is well measured in index A*. Along with the horizontal component, the vertical component of asymmetry was incorporated in indices A1 and A2. In this present paper, the vertical asymmetry of river channel cross-section of a moribund deltaic channel has been examined through indices A1 and A2 and compared with ideal width-depth ratio.